Accuracy of Pipelle Endometrial Samplingin comparison to D&C in women with abnormal uterine bleeding: A comparative analysis of all samples vsonly adequate samples by Pipelle - Sahar Salahuddin Amir, Sonia Aziz, Rabia Mukhtar, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The Pipelle endometrial sample biopsy (PESB) is considered the most convenient, non - invasive method for endometrial sampling. The abnormal uterine bleeding has many causes and consequences in women. The exact causes are described by histology of sample through D&C. The accuracy of PESB is under observation in different settings and a lot of work is further required. Aim: To see the accuracy of PESBin comparison to D&C for morphological findings among women with abnormal uterine bleeding. Study design: Cross--sectional analytical study. Place and duration of study: Gyne OPD & Histopathology Departments, Shaikh Zayed Hospital, Lahore during 1st May 2019 to 8th December 2019. Methodology: Two hundred and thirty five adult women with AUB recommended for D&C and with Pipelle endometrial sample were included. Those with endometrial thickness less than 4mm, having fibroids, with pelvic inflammatory disease, or clotting factor disorders were excluded. Pipelle endometrial sample was taken in GyneOPD and were examined at Histopathology Department. Data were managed through SPSS-20. Results: 80.0% had adequate Pipelle samples and Pipelle inadequate as negative were considered for comparison the accuracy of Pipelle for proliferative endometrium and secretory endometrium were lower (90.6% vs 100.0%) and (93.6% vs 100.0%) as compared to only 188 adequate samples considered; by considering D&C as gold standard. Accuracies for Hyperplasia, and chronic endomitritis were little higher for all cases and for carcinoma the accuracy was 100.0% in either case. Conclusion: Pipelle endometrial sampling can be considered an effective method for endometrial sampling with an accuracy of more than 90.0% for each of the endometrial morphology. Keywords: Abnormal uterine bleeding, Pipelle endometrial biopsy, Diagnostic accuracy